Church and war in the theology of Karl Barth - Rasmusson, Arne (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
The issues around church and war followed Karl barth during his whole career. His most extensive and systematic discussions of war are found in the Church Dogmatics. Here he questions the naturalness of war and develops a theologically motivated understanding of the practical primacy of pacifism for the disciples of Christ. However, his discussion of possible exceptions qualifies the main line of his argument to such an extent that the latter loses most of its content. His practical imagination was shaped by established semi-national churches and by his native Switzerland. This disjunction between his central theological account and his practical reasoning helps explain why his thoughts on war have been used by proponents of radically different positions. What is lacking is a display of the sort of church life and practice this kind of thinking presupposes. This is true whether one emphasises the main pacifist argument or develops barth’s thought in the direction of the just war tradition.